Criteria for Determining the Author of the Speech as a Problem of Theoretical Linguistics - Dedakhanova Muazzam Altmishbayevna (International Journal on Integrated Education, 2022)
This article is devoted to the description of the state and possible ways of developing linguistic theories through the prism of parameters determined by forensic linguistic expertise. Finding the true author of oral and written speech is a matter of great importance in terms of finding justice and ending injustice. It is natural that the research conducted in this direction will serve the development of this field, and will be the basis for achieving effective results in investigations and court proceedings.